2021
DOI: 10.2105/ajph.2020.306035
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Coverage and Preexposure Prophylaxis (PrEP) Use Among Men Who Have Sex With Men Living in 22 US Cities With vs Without Medicaid Expansion, 2017

Abstract: Objectives. To compare health care coverage and utilization between men who have sex with men (MSM) in Medicaid expansion versus nonexpansion states. Methods. We used cross-sectional weighted data from the National HIV Behavioral Surveillance system, which used venue-based methods to interview and test MSM in 22 US cities from June through December, 2017 (n = 8857). We compared MSM in Medicaid expansion versus nonexpansion states by using the Rao-Scott χ2 test stratified by HIV status. We used multivariable l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 20 publications
4
19
0
Order By: Relevance
“…The MOR (=1.40) suggests that at least 50% of the odds of PrEP use between multiple pairs of identical individuals living in different states are 40% greater or higher, on average, for individuals living in states with Medicaid expansion. This finding is in line with previously reported effect estimates of PrEP use in relation to Medicaid expansion 16–18. However, our final model ICC indicated that the state of residency of a given participant accounted for only 4% of the variance of PrEP use in our analysis, and the IOR-80 for our Medicaid expansion variables measure of association (ie, OR) included the null value—1.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The MOR (=1.40) suggests that at least 50% of the odds of PrEP use between multiple pairs of identical individuals living in different states are 40% greater or higher, on average, for individuals living in states with Medicaid expansion. This finding is in line with previously reported effect estimates of PrEP use in relation to Medicaid expansion 16–18. However, our final model ICC indicated that the state of residency of a given participant accounted for only 4% of the variance of PrEP use in our analysis, and the IOR-80 for our Medicaid expansion variables measure of association (ie, OR) included the null value—1.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with previously reported effect estimates of PrEP use in relation to Medicaid expansion. [16][17][18] However, our final model ICC indicated that the state of residency of a given participant accounted for only 4% of the variance of PrEP use in our analysis, and the IOR-80 for our Medicaid expansion variables measure of association (ie, OR) included the null value-1. In MLA, the inclusion of the null value on the IOR-80 indicates that the variable was not relevant to understanding the state-level variation in an individual predisposition to use PrEP.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our findings provide evidence that Medicaid expansion though the Affordable Care Act may have been effective at facilitating PrEP use among the partners of PWH, as has been found for PrEP use in general [36,37]. Although reported partner PrEP use was similar during the 2015 cycle, it increased at higher rates among PWH living in jurisdictions that expanded Medicaid than among those living in jurisdictions that did not, and by the 2019 cycle the prevalence was higher among those in Medicaid expansion states (26.8 vs. 20.4%).…”
Section: Discussionsupporting
confidence: 60%
“…Multiple studies have found increased PrEP coverage and use in states that expanded Medicaid, and 1 study reported a 5% decrease in the rate of HIV diagnoses among states that expanded Medicaid. 49,100,101 Oral PrEP coverage without cost sharing is now mandatory after the 2019 grade-A recommendation by the U.S. Preventive Services Task Force. 102 The approaching introduction of widespread generic tenofovir/emtricitabine may also impact PrEP costs and uptake.…”
Section: Structural Levelmentioning
confidence: 99%